(3TQM aUhd CHbQGWs - (3YdGA GdOjf Ydj Hf CHi GdMRe GdbQTi , GHf GdfajSs; (3GHf CHj GdSYhO , eMeO Hf UGdM CHj GdSYhO GdSHGYj GdMafGhj,J (B1268 (3g` s ((3GHf SdGeI Hf Nda s)
(3ChdgG (B:s
(3CeG HYO (B: (3Zf eG bO Sda ef TQhMfG dgPG GdcJGH , aEf fSNI JNJda HMSH GNJdGa CZQGV GdWGdHjf dg s
(3BNQgG (B:s
(3dCf eG jMJGLhf Edi ENQGLg ef GdQWhHGJ GdQOjFI eeG gh ai GdeYOI hfhGMjgG , heJi cGf Pdc hLH Cf jchf GdGSJaQGZ HGdbF hgh GdeQGO HGdGSJaQGZ ef ahb s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs